Paciente de sexo masculino de 72 años de edad con diagnóstico de hipertensión arterial e insuficiencia renal crónica. - Jiménez Peñafiel, Bryan Josué (2021)
The present case study refers to a 72-year-old male patient with a diagnosis of arterial hypertension and stage III chronic renal failure. The patient underwent a comprehensive and individualized nutritional assessment, the patient was evaluated using anthropometric, biochemical, clinical and dietary indicators. In the anthropometric indicator, data of weight 74.4 kg, height of 174 cm, BMI of 24.6 kg / m2 with interpretation of normal stage according to WHO, waist circumference of 95 cm, hip of 102 cm were obtained. In addition, the patient was assessed using bioimpedance values, obtaining data on body fat of 16.6% (normal), metabolic age of 56 years, percentage of visceral fat of 9% (normal), muscle percentage of 36.7% (normal). In the biochemical evaluation, urea values of 63.9 mg / dl and creatinine of 1.99 mg / dl were observed, which were high, they were results to be expected because these biochemical parameters are the ones that are most altered in chronic renal failure. In the clinical evaluation, no major alteration was observed, only blood pressure of 120/80 mmHg. In the dietary aspect, the patient was prescribed a diet according to the patient's conditions, whether they be socioeconomic, nutritional and his preference, for which he was assigned a diet of 1900 kcal, hypoodic and controlled in sodium and potassium. At the end of this study, the patient is monitored and followed up to verify that there are positive advances that influence the education not only of the patient but also of his family in general.